HUBUNGAN ANTARA TINGKAT STRES DENGAN INTENSITAS MEROKOK PADA MAHASISWA DI UNIVERSITAS NEGERI MEDAN - Cindi Kezia Simbolon; Rachel Nadia S.B. Banjarnahor; Tamasya Mercy Raja Guk Guk; Syaukani Ali Arkan; Maria Benedicta florenta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between stress levels and smoking intensity among students at Universitas Negeri Medan. The background of this research is based on the assumption that stress is one of the factors that may influence smoking behavior, particularly among university students who face various academic and social demands. This research employed a quantitative approach with a correlational method. The population consisted of students at Universitas Negeri Medan, with a total sample of 32 respondents selected using a specific sampling technique. Data were collected through questionnaires measuring stress levels and smoking intensity. The obtained data were then analyzed using the Pearson Product Moment correlation and simple linear regression with the assistance of SPSS software. The results indicated that there was a positive relationship between stress levels and smoking intensity; however, the strength of the relationship was low, as reflected by a correlation coefficient of 0.271. Furthermore, the significance value was 0.133 (p > 0.05), indicating that the relationship was not statistically significant. The results of the simple linear regression analysis also revealed that stress levels did not have a significant effect on smoking intensity, with a contribution of only 7.4% to the variance in smoking intensity. In conclusion, stress levels are not a primary factor influencing smoking intensity among students. Therefore, further research is recommended to include other variables that may have a stronger influence on smoking behavior.